Thinking Bigger and Better about "Bad Apples": Evolutionary Industrial/Organizational psychology and the Dark Triad - JONASON, Peter K. (Institutional Knowledge at Singapore Management University, 2014)
The focal article by Guenole (2014) correctly contends that industrial–organizational (I–O) psychology has been overly reliant on the Big Five or the five-factor model (Benet-Martínez & John, 1998). Although popular and useful, the Big Five also tends to be limited in two important ways. The Big Five is a set of atheoretically derived, descriptive adjectives, and it tends to better tap “positive” aspects of people's personality over “negative” or “darker” sides. A number of authors have highlighted the importance of examining “darker” aspects of people's personality both outside (Jonason, Li, Webster, & Schmitt, 2009; Lee & Ashton, 2005; Paulhus & Williams, 2002) and within (Hogan & Hogan, 2001; Jonason, Slomski, & Partyka, 2012) the workplace. As potential mechanisms to explore the “darker” aspects of the workplace, the author of the focal article suggests the Dark Triad of personality (i.e., narcissism, psychopathy, and Machiavellianism). Although the focal article was not solely about these three, we use them as examples to illustrate a broader point: An evolutionary perspective can provide a foundational theory through which workplace phenomenon can be examined with greater richness.